(untitled) (Bangladesh Journal of Pharmacology, 2010)
Ethanolic extract of the roots of C. spinarum was evaluated for hepatoprotective and anti-oxidant activities in rats. Oral pre-treatment with ethanolic extract (100, 200 and 400 mg/kg) showed significant hepatoprotective activity against CCl4 and paracetamol-induced hepatotoxicity by decreasing the activities of bilirubin and lipid peroxidation, and significant increase in the levels of uric acid, glutathione, super oxide dismutase, catalase and protein in a dose dependent manner, which was confirmed by the decrease in liver wet weight and histopathological examination. The extract possessed strong anti-oxidant activity. This suggests that the hepatoprotective activity of C. spinarum is possibly attributed to its free radical scavenging properties.